Double vaccine to control livestock diseases - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Two of Africa's most crippling livestock diseases will soon be controllable by a single vaccination. Rinderpest and capripox (lumpy skin disease of cattle, sheep pox and goat pox) cause serious loss of productivity and can lead to mortality rates...